Usage-based approaches to language acquisition and language teaching - Evers-Vermeul, Jacqueline; Tribushinina, Elena (Studies on Language Acquisition SOLA., 2017)
Language acquisition is a human endeavor par excellence. As children, all human beings learn to understand and speak at least one language: their mother tongue. It is a process that seems to take place without any obvious effort. Second language learning, particularly among adults, causes more difficulty. The purpose of this series is to compile a collection of high-quality monographs on language acquisition. The series serves the needs of everyone who wants to know more about the problem of language acquisition in general and/or about language acquisition in specific contexts.